Negacyclic codes of length 2k over. Issue 3 (4th March 2017) - Bandi, Rama Krishna; Bhaintwal, Maheshanand
ABSTRACT: In this paper, we study negacyclic codes of length2 k over the ringR = Z 4 + u Z 4, u 2 = 0 . We give the complete structure of negacyclic codes and determine their cardinalities. The structure of the duals of negacyclic codes is determined and self-dual negacyclic codes are characterized. We present some new goodZ 4 − liner codes which are the Gray images of negacylic codes over R .